Damping factor in magnetorheological shear stiffening gel: Fabrication and formulation of a fractional constitutive model - Fei Guo; Youmei Yu; Xiaoguo Lin; Chengbin Du (PLoS ONE, 2025)
A variety of magnetorheological shear stiffening gels (MRSSGs) were synthesised by incorporating varying amounts of carbonyl iron powder (CIP) into a shear stiffening gel (SSG) matrix. The dynamic damping performance of the MRSSG was initially evaluated using a rheometer. The damping factor of MRSSGs demonstrates magnetic-sensitive characteristics and can autonomously respond to external stimuli due to B-O cross-linked bonds. The examination of the effects of applied frequency and magnetic field on the damping factor included the delineation of viscous damping from the SSG matrix, magneto-induced damping, and interfacial damping, leading to the development of an innovative fractional constitutive model. This model explicitly illustrates the relationship among the damping factor, shear angular frequency, and magnetic field strength. Theoretical results of the damping factor, derived from modelling calculations and analyses, closely align with experimental findings as excitation angular frequencies vary across different magnetic induction intensities, exhibiting a high fitting accuracy with a correlation coefficient exceeding 0.999. Furthermore, an augmentation in magnetic induction strength correlates with a reduction in the fractional order value, which declines from 0.96 to 0.49.